Case-Based Teaching in Obstetric and Gynecology - Dayangku Norlida, Awang Ojep; Manjubala S, Talekar (Mini Sood, Doctor's Apartments, Vasundhara Enclave, Delhi - 110096, 2024)
Book Chapter Section III: Gynecological Pathology Cases: 1. Molar Pregnancy 2. Cervical Polyp 3. Dysfunctional uterine bleeding 4. Mature cystic teratoma 5. Fibroid uterus 6. Squamous cell carcinoma 7. Dysgerminoma